kondisi karang dan ikan karang pada empat daerah penyelaman yang sering dikunjungi pada wisata bahari di taman nasional bunaken - Jongky Wuner Alfius Kamagi; Frans Victor Rattu (Faculty of Economics and Business, University of Mataram, 2024)
Bunaken National Park is one of the special interest tourism destinations with diving as its main attraction. Bunaken National Park is not only famous for its diversity of marine biota, such as fish, mammals, and marine reptiles, but also for the uniqueness of marine animals such as pygmy seahorses and nudibranchs. Bunaken National Park, especially on Bunaken Island, is also famous for its unique underwater landscape in the form of coral reef walls. The purpose of this study was to see the condition of coral cover and the diversity of reef fish in 4 diving areas on Bunaken Island. The data collection locations were Pangalisang, muka kampung, Likuan 3 and Fukui. Data were taken using the Line Transect and visual census. The results obtained were that the coral conditions in the Pangalisang, Likuan 3, and Fukui diving areas were in good condition, while the Muka Kampung area was in moderate condition. The diversity index in these 4 diving areas is moderate